Analysing Epistemic Disparity: The Use of Possible-World Theory in the Identification of Rhythmic Strategies - Fenice, Andrea (Status Quaestionis, 2020)
This article discusses the integration of semiotic rhythm analysis with the theory of possible worlds. The complex issue of analysing rhythm in narrative texts has been tackled by Daniele Barbieri with his theory based on ‘textual relief’, an adaptive theoretical tool for identifying and investigating rhythmic strategies at all textual levels and across different media. Narratology, with its in-depth description of narrative strategies concerning worldbuilding, can contribute to a great extent to this endeavour. Merging the two theories, a detailed analysis of narrative choices can be performed, with a specific focus on the narrator’s strategies concerning withholding and divulging information to the recipient. Offering a theoretical overview and specific examples of different narratorial strategies, this paper examines several ways in which narrators can exploit the epistemic disparity between the recipient’s knowledge and their own to manage tension and suspense, thus creating textual relief.